Chapter De Moluccis insulis. Un resoconto propagandistico ante-litteram - Vezzosi, Letizia (Studi e saggi, 2021)
The image of Magellan as a modern hero who strongly wanted and tried at any price to complete the circumnavigation of the earth, but whom death prevented from doing so partly arose as soon as the first reports of the journey following the arrival of the only ship, Victoria, with 18 survivors were issued. Among these, there is the account Maximilianus Transylvanus gave on the basis of the information obtained interviewing a group of survivors, including Captain Elcano. He immediately understood the political relevance and the propaganda potential of the success of Magellan's enterprise. In this article we will analyze De Moluccis insulis, highlighting the content and linguistic choices that contribute to creating an image of the expedition, of Magellan and of the role of Spain in the new world.